The Inductive Method and Analytical Approaches in Comparative Public Administration Studies: A Public Administration Perspective on the U.S. Administrative System - Sri Yulianty Mozin; Alexander Badjuka; Ni Made Amanda; Dea Ayu Lestari; Utami Septiyani Dumbela; Moh Prayuda Sampara (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the application of the inductive method and various approaches in the comparative study of public administration, highlighting the administrative system of the United States as a case study. The inductive approach is employed to identify emerging patterns and principles from empirical facts, while the comparative approach enables cross-country analysis that enriches the understanding of variations in public administration systems. This research adopts a qualitative method with an emphasis on literature review and document analysis. The findings indicate that the inductive method offers a high degree of analytical flexibility, whereas the historical, structural, and institutional approaches provide comprehensive conceptual frameworks for assessing public administration systems. The examination of the United States administrative system reveals key characteristics such as federalism, the principle of checks and balances, and strong decentralization. These findings carry implications for developing countries in designing adaptive administrative systems grounded in good governance.